Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
y=0 nha bạn toán tiếng anh đúng không
2.3x3,4+2,3x5,6x2,3 =2,3x3,4+2,3x5,6x2,3x1 =2,3x(3,4+5,6+1) =2,3x10 =23
Giải
=2,3 x 3,4 + 2,3 x 5,6 + 23 x 1
= 2,3 x (3,4 + 5,6 + 1)
=2,3 x 10
=23
2.3x3,4+2,3x5,6x2,3 =2,3x3,4+2,3x5,6x2,3x1 =2,3x(3,4+5,6+1) =2,3x10 =23
f,F=3. (1/2 .3 + 1/3.4 +...+ 1/99.100)
= 3. (1/2 - 1/3 + 1/3 - 1/4 + 1/4 - 1/5 +...+ 1/99 - 1/100
= 3. (1/2 - 1/100)
= 3. 49/100
= 147/100
g, G = 5/3. (3/1.4 + 3/4.7 +...+ 3/61.64)
= 5/3 . (1 - 1/4 + 1/4 - 1/7 +...+ 1/61 - 164
= 5/3 . (1-1/64)
= 5/3 . 63/64
= 105/64
f, \(F=\frac{3}{2.3}+\frac{3}{3.4}+...+\frac{3}{99.100}\)
\(\Leftrightarrow F=3\left(\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{99.100}\right)\)
\(\Leftrightarrow F=3\left(\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{99}-\frac{1}{100}\right)\)
\(\Leftrightarrow F=3\left(\frac{1}{2}-\frac{1}{100}\right)\)
\(\Leftrightarrow F=3\left(\frac{49}{100}\right)=\frac{147}{100}\)
g, \(G=\frac{5}{1.4}+\frac{5}{4.7}+...+\frac{5}{61.64}\)
\(\Leftrightarrow G=5\left(\frac{1}{1.4}+\frac{1}{4.7}+...+\frac{1}{61.64}\right)\)
\(\Leftrightarrow G=5.\frac{1}{3}\left(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{61}-\frac{1}{64}\right)\)
\(\Leftrightarrow G=\frac{5}{3}\left(1-\frac{1}{64}\right)\)
\(\Leftrightarrow G=\frac{5}{3}.\frac{63}{64}=\frac{105}{64}\)
\(G=\frac{5}{1.4}+\frac{5}{4.7}+...+\frac{5}{61.64}\)
\(\Rightarrow G=\frac{5}{3}.\left(\frac{3}{1.4}+\frac{3}{4.7}+\frac{3}{7.10}+..+\frac{3}{61.64}\right)\)
\(\Rightarrow G=\frac{5}{3}.\left(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+..+\frac{1}{61}-\frac{1}{64}\right)\)
\(\Rightarrow G=\frac{5}{3}.\left(1-\frac{1}{64}\right)=\frac{5}{3}.\frac{63}{64}\)
\(\Rightarrow G=\frac{5.63}{3.64}=\frac{5.21.3}{3.64}=\frac{5.21}{64}=\frac{105}{64}\)
870 - x : 11 x 87 = 261
x : 11 x 87 = 870 - 261
x : 11 x 87 = 609
x : 11 = 609 : 87
x : 11 = 7
x = 7 x 11
x = 77
x : 0.25 x 2.3 = 6.9
x : 0.25 = 6.9 : 2.3
x : 0.25 = 3
x = 3 x 0.25
x = 0.75
2 x (y + y) = 8.16
y + y = 8.16 : 2
y x 2 = 4.08
y = 4.08 : 2
y = 2.04
y x 1.5 + y + y x 7.5 = 59.8
y x (1.5 + 1 + 7.5) = 59.8
y x 10 = 59.8
y = 59.8 : 10
y = 5.98
m : 1/6 + m : 0.25 = 152
m : 1/6 + m : 1/4 = 152
m x 6 + m x 4 = 152
m x (6 + 4) = 152
m x 10 = 152
m = 152 : 10
m = 15.2
m : 1/3 + m : 0.25 = 1.4
m : 1/3 + m : 1/4 = 1.4
m x 3 + m x 4 = 1.4
m x (3 + 4) = 1.4
m x 7 = 1.4
m = 1.4 : 7
m = 0.2
\(\frac{3}{1.2}+\frac{3}{2.3}+...+\frac{3}{49.50}\)
= \(3.\left(\frac{1}{1.2}+\frac{1}{2.3}+..+\frac{1}{49.50}\right)\)
= \(3.\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+..+\frac{1}{49}-\frac{1}{50}\right)\)
= \(3.\left(1-\frac{1}{50}\right)\)
= \(3.\frac{49}{50}\)
= \(\frac{147}{50}\)
\(\frac{3}{1.2}+\frac{3}{2.3}+...+\frac{3}{49.50}\)
\(=3\left(\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{49.50}\right)\)
\(=3\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{49}-\frac{1}{50}\right)\)
\(=3\left(1-\frac{1}{50}\right)=3.\frac{49}{50}=\frac{199}{50}\)